أثر التطور العلمي على النسب - شيكوش محمد (المسيلة, 2023)
النسب أقوى الدعائم التي تقوم عليها األسرة، وهو قرابة اإلنسان وانتمائه إلى أبائه أجداده، وقد نال حظا وفيرا من عناية الشريعة اإلسالمية به والسعي إلى حفظه، واعتبرته مقصدا من مقاصدها الضرو رية 44/42 خصص فصال كامال التي حافظت عليها، كما أن المشرع الجزائري في قانون األسرة من األمر للنسب وخصص له المواد من أربعين إلى ستة وأربعين لتنظيمه وهذا يدل على أهمية النسب، غير أن التطورات العلمية الحديثة ألقت بظاللها على األسرة بصفة عامة وعلى النسب بصفة خاصة مما انعكس ذلك على الفرد والمجتمع، فكان لزاما على المشرع أن يساير هذا التطور ويجعل له شروط وضوابط لكي ال يخرج عن نطاقه المشروع، وهو ما يفرض علينا ضرورة وجود نصوص قانونية منظمة لهذه التقنيات اإلنساني والعلمي وتتحول إلى الجانب التجاري الذي يهدد كرامة اإلنسان. العلمية لكي ال تخرج من جانبها Summary: Descent is the most powerful pillar of the family, which is the kinship of man and his affiliation with his ancestral fathers; He has had great luck with Islamic law and seeking to preserve it. The Algerian legislature in the Family Code 02/05 devoted a full chapter to parentage and allocated articles 40 to forty-six to its organization, which demonstrated the importance of parentage. State-of-the-art scientific developments, however, have cast a shadow over the family in general and on descent in particular, as reflected in the individual and society, the legislator had to keep pace with this development and make it subject to conditions and controls in order not to depart from its legitimate scope. This requires us to have legal texts regulating these scientific techniques so that they do not emerge from the human and scientific side and turn into the commercial aspect that threatens human dignity
Keywords: أثر التطور العلمي - النسب